Peer Educators’ Roles and Challenges in Promoting Students’ Healthy Dietary Behavior in School-Based Nutrition Program - Tisa Rahma Sari; Lilis Permatasari; Luh Ade Wiradnyani; Judhiastuty Februhartanty (Media Gizi Indonesia, 2026)
Background: Adolescents in Indonesia face a triple burden of malnutrition which is aggravated by poor dietary behaviors. In West Java, adolescents commonly exhibit low dietary diversity, a habit of skipping meals, and frequent consumption of unhealthy snacks. The school setting offers strategic opportunities for health promotion through peer education. Objective: This study aims to explore the roles and challenges experienced by peer educators in promoting healthy dietary behavior in schools implementing the Nutrition Goes to School (NGTS) program in West Java. Methods: A qualitative study with an interpretive descriptive approach was applied. Data were collected through in-depth interviews with teachers and program stakeholders as well as focus group discussions involving peer educators and peer learners from each school. The data were analyzed thematically using NVivo 12. Results: The findings indicate that peer educators perform diverse and adaptive roles, including acting as healthy school advocates, health educators, influencers, role models, and school-based health facilitators. However, they encountered both internal and external challenges. Internally, they experienced low motivation, difficulty in maintaining healthy behavior, and lack of confidence. Externally, barriers included peer ignorance, limited availability of healthy food option at school, limited continuous training, and poor coordination with related stakeholders. Conclusion: These findings highlight the essential role of peer educators in promoting healthy dietary behavior, while underscoring the need for stronger institutional frameworks, continuous training, and improved collaboration between schools, stakeholders and families to ensure the sustainability of school-based nutrition programs.